The Predictability of the Sources of Psychological Stresses Upon Marital Adjustment Among a Sample of Married Couples - Shawashrah, Omar; Abo Jolban, Moawiah (Jordan Journal of Educational Sciences, 2019)
The present study aimed at revealing the level of psychological stress and adjustmant among married teachers in Ajloun Governorate, and identifying the correlation between the sources of stress and marital adjustmen, in order to disclose the predictive ability of the sources of psychological stress in the interpretation of marital adjustment. The sample of the study consisted of 252 teachers (146 male, 106, female), selected by available sample. To achieve the aims of the study, two measures were developed: A measure of sources of psychological stress and a measure of marital adjustment. The validity and reliability were conducted for both measures, and then applied to the study sample. The results showed that the level of psychological stress sources among married teachers was average, and the level of marital adjustment was low. The results indicated that there were no statistically significant differences in the level of psychological stress and martial adjustment by the variables of (age and gender) among teachers. However, the results revealed a statistically significant relationship between the sources of total stress, and marital adjustment among teachers. Family strossers, personal stressors’ and social strossers were found to be the most significantly predicted variables of marital adjustment among teacher, while, work related stressors has no predicted power of marital adjustment among teachers